Student Evaluation in the Subject of Technology in Primary Schools in Slovakia - Lukáčová, Danka; Botló, Patrik (Journal of Education Culture and Society, 2024)
Aim. School evaluation is a sensitive process that involves teachers, students, and their parents in various ways. This article focuses on researching student evaluation by teachers in the subject of Technology in Slovak primary schools. The research aims to determine how teachers assess students in the subject of Technology.Methods. As a research tool, we used a self-designed questionnaire for teachers. We analysed the respondents' answers using descriptive statistical methods. To ascertain differences in responses between qualified and unqualified teachers, we employed the chi-square test.Results. By analysing the data obtained from 107 questionnaires, we found that technology teachers mostly employ an individual approach when evaluating students and emphasise the practical aspects of the subject. Among the evaluation methods, grading scales for summative student assessment prevail. At the same time, there were statistically significant differences between qualified and unqualified teachers. We also observed statistically significant differences in evaluations between qualified and unqualified teachers.Conclusion. For this reason, it is necessary to ensure an increase in the number of qualified and internally motivated technology teachers in primary schools, as only such teachers can motivate and inspire their students to pursue this field of study.